Low-rise office retrofit: prerequisite for sustainable and green buildings in Shanghai - Hong, Y.; Deng, W.; Ezeh, Collins I. (2019)
Commercial buildings comprise of 25% office blocks, largest proportion in commercial sector with highest energy consumption in Shanghai. Nevertheless, the demand for office space is still rising, driven by state-owned enterprises. Unfortunately, these existing buildings are energy inefficient as they barely adapt to present varying climate conditions of the province. Owing to aggravated climate change and rising urbanization rate of Shanghai, attention should be directed towards upgrade of office buildings to meet set sustainable building standards. 3-dimensional spatial characterization using vector topographic mapping posits low-rise buildings account for more than 50% of total buildings in Shanghai. Hence, retrofitting existing low-rise office buildings will significantly contribute to building sustainability. Subsequently, a retrofit package guideline suitable for sporadic energy use mode in rapidly expanding cities like Shanghai should be established. This nascent study postulates an updated correlation between climate change and building energy consumption in Shanghai. Based on the postulation, it is recommended that the best energy conserving building retrofit package is that which can mitigate the impact of both societal factors (like urbanization rate) and climate change to building energy consumption. In general, this study defines a foundation framework for building researchers and decision-makers to effectively evaluate retrofit measures for existing buildings become sustainability in Shanghai.